Motivation, Vision, and Gender: A Survey of Learners of English in China. Issue 1 (6th October 2015) - You, Chenjing (Julia); Dörnyei, Zoltán; Csizér, Kata
Abstract: This study reports on the second phase of a large‐scale stratified survey in China, examining the role of vision and imagery in the learners' motivation to learn English as a foreign language. Understanding visualization has been a featured area of recent developments in second language (L2) motivation theory, and this study is the first to offer a broad overview of the extent to which the capacity of vision contributes to the overall motivational setup of a whole language learning community. Besides surveying several imagery‐related variables in an extensive sample of Chinese secondary school and university students ( N > 10, 000) by comparing male and female Chinese L2 learners' (often different) motivational dispositions with and without any prior visualization experience, the study also explores the visionary trajectories of learners who reported positive and negative changes in their imagery capacity over time, thereby examining the impact of the change in vision on motivational development. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki